Private Monitoring, Collusion and the Timing of Information - Fahad Khalil; Jacques Lawarrée; Troy J. Scott (Center for Economic Studies and ifo Institute (CESifo), 2013)
When the information used by a principal to monitor an agent is private, and thus non-verifiable by a third party, the principal has a credibility issue with the agent. The agent should be concerned that the principal could misrepresent the information in order to collect a monetary penalty from him. Restoring credibility may lead to an extreme waste of resources the so-called burning of money, where the monetary penalty is given away to a third party. We show that a more realistic and efficient outcome is feasible by exploiting the timing of private information. If the private information arrives before the agent has completed his effort, non-monetary tools like rescaling the project become optimal, and no money needs to be burned. We show that rescaling is more effective than pure monetary penalties because effort has different values to different parties, while money is equally valuable to all parties. An alternative way to solve the principal's credibility problem is to certify the private signal and make it public. When collusion between the certifier and the agent is an issue, we uncover interesting similarities between private signals and public (certified) signals vulnerable to collusive manipulation. We show that certification of private information by a third party may not always be in the interest of the principal if this certification raises the specter of collusion.
Keywords: D73; D82; D86; 330; monitoring; unverifiable signal; certification; private communication; timing of information; collusion; non-monetary penalties; burning money